Cultural Politics of Hygiene in India, 1890-1940 - Prasad, Srirupa. author. aut Link
X, 142 p.
Keywords: This book examines genealogies of contagion in between contagion as microbe and contagion as affect. It analyzes how and why hygiene became authoritative and succeeded in becoming a part of the broader social and cultural vocabulary within the colonialist, anti-colonial, as well as modernist discourses.